Shaping attosecond pulses by controlling the minima in high-order harmonic generation through alignment of CO2 molecules - Jin, Cheng; Wang, Su-Ju; Zhao, Xi; Zhao, Song-Feng; Lin, C. D. (My University, 2020)
We report a simple method for generating shaped attosecond pulses by using a CO2 molecule. Unlike most other molecules, owing to its unique energy and angle dependence and the presence of deep minima in the photoionization transition dipole moment, the shape of harmonic spectra, especially the position and depth of minima, can be readily controlled by tuning the degree of alignment. The sensitive alignment dependence of the minima is due to the coherent interference of a laser-induced dipole from each molecule when CO2 molecules are moderately aligned, but not when they are well aligned or when they are isotropically distributed. Such a sensitivity offers a simple way of controlling the spectral amplitude and phase of the generated harmonics and thus shaping the generated attosecond pulses, for example, producing structured attosecond pulses by splitting a single burst into two. We illustrate how such pulses are generated and how to characterize them. This method offers a simple way to shape attosecond pulses at the generation step. It can be easily implemented experimentally to generate attosecond pulses with strong phase variations for unique applications.